(untitled) (Scientific journal of the Fergana State University, 2023)
In the paper an analogue of the Gursat problem was investigated for a non classical fourth order partial equation with singular coefficients. To solve the problems, we applied the two-dimensional generalized Erdeyi-Kober operator. The solution is shown explicitly.